1983
DOI: 10.1111/j.1438-8677.1983.tb01713.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Morphogenesis of Sun and Shade Plants Iii. The Combined Effects of Light Intensity and Nutrient Supply

Abstract: In three experiments the effects of light intensity and nutrient supply (nitrate or phosphate) and their combined effects on the growth and morphogenesis of two shade-tolerant plant species and a non-tolerant species were studied. Nutrient supply was limited by placing the plants on a standard nutrient solution for a limited period each day and placing them on a nitrogen-free or phosphate-free solution for the rest of the day. The effects of light intensity and nitrate supply on growth and morphogenesis showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 28 publications
4
18
0
Order By: Relevance
“…In previous studies, similar results were found in that RGR differences were ascribed only to NAR (Eagles, 1967;Pons, 1977), only to LAR (Higgs and James, 1969;Dijkstra, 1989;Smeets and Garretsen, 1986), or to both NAR and LAR together (Jarvis and Jarvis, 1964;Corrẽ, 1983). In particular, differences in light intensity between the two environments likely influenced the relative contributions of NAR and SLA to RGR.…”
Section: Discussionsupporting
confidence: 81%
“…In previous studies, similar results were found in that RGR differences were ascribed only to NAR (Eagles, 1967;Pons, 1977), only to LAR (Higgs and James, 1969;Dijkstra, 1989;Smeets and Garretsen, 1986), or to both NAR and LAR together (Jarvis and Jarvis, 1964;Corrẽ, 1983). In particular, differences in light intensity between the two environments likely influenced the relative contributions of NAR and SLA to RGR.…”
Section: Discussionsupporting
confidence: 81%
“…It is well-known that the functional equilibrium between shoot and root (Brouwer, 1963) may be expressed in the respective masses and specific activities of above-and under-ground parts of the plant (Corr6, 1983). Reproductive plants of P.lanceolata are assumed to have a reduced overall photosynthetic activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies, analysing the data from differing perspectives, did not test whether the proportional impact of drought on RGR differed across irradiance treatments. Because dry mass yield is an exponential function of RGR (Evans 1972), a greater impact of drought on yield can arise at higher irradiance, even when resource-levels have independent, multiplicative effects on RGR (Corré 1983), especially when RGR is high, i.e. for fast-growing species.…”
Section: Orthogonal Impacts Of Shade and Droughtmentioning
confidence: 99%